DNA Testing in Determining the Lineage of Children Born Out of Wedlock: A Maqāṣid al-Sharī‘ah Perspective - Mohammad Arjati Firmansyah; Abd Rouf (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
The determination of lineage (nasab) for children born out of wedlock remains a contested issue in Islamic family law, particularly regarding the admissibility of DNA testing as legal evidence. This study examines the legal position of DNA testing in determining the lineage of children born out of wedlock and analyzes its implications from the perspective of maqāṣid al-sharī‘ah. This study employed normative legal research with descriptive-analytical characteristics using conceptual, statutory, and comparative approaches. Data were collected through library research and analyzed qualitatively using inductive-deductive reasoning. The findings reveal that DNA testing possesses strong scientific validity in establishing biological relationships and may function as corroborative evidence in lineage determination. However, within Islamic law, DNA testing cannot independently establish nasab shar‘i, as legal lineage remains contingent upon lawful marriage. From the perspective of maqāṣid al-sharī‘ah, DNA testing supports the realization of ḥifẓ al-nasl (protection of lineage), ḥifẓ al-nafs (protection of life), and ḥifẓ al-‘irḍ (protection of dignity) by ensuring biological certainty, protecting children’s rights, reducing social stigma, and strengthening parental responsibility. Nevertheless, its application also presents potential risks, including genetic data misuse, privacy violations, and family conflict. This study concludes that the benefits of DNA testing outweigh its potential harms, provided that its implementation remains limited, legally regulated, and accompanied by strict protection of personal genetic data. Therefore, DNA testing should be positioned as a modern evidentiary instrument that supports the realization of maqāṣid al-sharī‘ah without replacing the legal requirements of lineage recognized in Islamic law.